2016
DOI: 10.1007/s10897-016-9958-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Psychosocial Effects of WES Test Results on Parents of Children with Rare Diseases

Abstract: The use of whole exome sequencing (WES) for diagnostics of children with rare genetic diseases raises questions about best practices in genetic counselling. While a lot of attention is now given to pre-test counselling procedures for WES, little is known about how parents experience the (positive, negative, or inconclusive) WES results in daily life. To fill this knowledge gap, data were gathered through in-depth interviews with parents of 15 children who underwent WES analysis. WES test results, like results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
99
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(120 citation statements)
references
References 26 publications
19
99
0
2
Order By: Relevance
“…Similar to studies on reactions to CMA and CES testing that have reported parental feelings of relief, better ability to cope with guilt, but also worry and a loss of hope for the future, our results indicate that CES elicits many different emotions in parents. While frustration, worry and fear were some of the most frequent emotions reported upon learning results, curiosity and relief were reported nearly as often.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to studies on reactions to CMA and CES testing that have reported parental feelings of relief, better ability to cope with guilt, but also worry and a loss of hope for the future, our results indicate that CES elicits many different emotions in parents. While frustration, worry and fear were some of the most frequent emotions reported upon learning results, curiosity and relief were reported nearly as often.…”
Section: Discussionsupporting
confidence: 88%
“…Parents express a duty to pursue testing and feelings of worry and relief regardless of their child's results; and acceptance, empowerment, and more focused care when results identify a diagnosis . Parents also report isolation and loss of hope about the future, particularly when the diagnosis is novel or rare, but are accepting of uncertain information . While parents endorse the potential of CES as a diagnostic tool and many want to learn secondary results, some are ambivalent about learning uncertain results .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the genetic counselor ensures that the families have a reasonable expectation of the ways in which a genetic test result may or may not inform clinical care, and addresses the psychosocial implications of genetic testing. 15 The epileptologist and genetic counselor work together to design and implement a plan for genetic testing, interpret genetic test results, and make recommendations for follow up.…”
Section: Epilepsy Genetics Clinicmentioning
confidence: 99%
“…Furthermore, due to methodological limitations, WES may not always be the correct test to order as WES will not detect all genetic causes of disease (eg, it will not detect chromosomal structural differences) 14. Both informative and uninformative results can lead to complex patient and family psychosocial repercussions15 and could impair future insurability. Genetic counselling facilitates informed decision making.…”
Section: Don’t Order Whole Exome Sequencing (Wes) Prior To Genetic Comentioning
confidence: 99%